Consumer assessment of the level of performance of used clothing a market survey in Baguio City - Mabazza, Zherilleen Halili
The used clothing business in Baguio City is an unusual phenomenon that deserves a special attention from researchers. This is such a research. The main problem of this study is, "How do consumers assess the performance of used clothing?" Included in this main problem are subtopics about how the functions of clothing performance are related to socioeconomic indicators such as age, income, occupation, and civil status, how clothing functions affect buyer decisions, and how the performance of clothing functions cause satisfaction and their failed performance cause dissatisfaction. Clothing mainly has six performance functions. These are clothing (1) as protection from the environment, (2) as an enhancement of sexual attraction, (3) for aesthetic and sensuous satisfaction, (4) as an indicator of status, (5) as an extension of self-image, and (6) as a medium of group acceptance. These buying motivations and choices of each individual toward clothing. A good performance of each function will mean a satisfied user, and likewise, a failed performance of each will be a cause of dissatisfaction with the garment. This thesis seeks answers about how these six functions affect buyer decision process. These process consist of five stages. These are (1) need recognition; (2) information search; (3) evaluation of alternatives; (4) purchase decision; and (5) postpurchase behavior. Additionally, this research attempts to fin out is the socioeconomic indicators age, occupation, and civil status affect consumer assessment of clothing performance. To arrive at the answers to the question presented above, a cross - sectional study that explores the extent of influence of clothing performance to buyer decisions is employed. A cross - sectional study is a research work whose distinguishing mark is that it is done at a single point on time only. Having this nature, this research describes this particular market scenario based from the data gathered at the single point in time, specifically, from 25 August - 18 September, 1999. My subjects are female consumers of used clothing from Baguio City, between the ages 18 - 32, and at least have received some college education. My data collection method is in instrument administration wherein the instrument is a questionnaire. This was distributed to 80 customers. Out of the 80 consumers who were given a questionnaire, 56 responded. This is a 70% response rate. The researcher used the Chi-Square Test of Independence or Goodness-of-Fit for hypothesis testing. This test consists of a hypothesis and a null hypothesis. The hypothesis contends that a consumer's age, occupation, and civil status affect her ratings of clothing functions. On the other hand, the null hypothesis asserts that there is no relationship between the two variables. The Chi-Square Test failed to support the hypothesis, that is, that a relationship exists. It cannot be concluded, though, that a respondent's age, occupation, and civil status do no affect her clothing decisions (or the null hypothesis) since future researches might prove otherwise. Due to this, averages or means was used to interpret data. No relationships are claimed using this method, though. Results show that he functions of clothing performance exert a slight influence in the respondent's preliminary stages of the decision process. They are very important in the last two stages, in Purchase Decision and Postpurchase Behavior stages, though. These are the most important stages since the satisfaction or dissatisfaction of a consumer is determined during these process. The results of the study indicate that the respondents rated the functions of clothing performance as a cause of satisfaction in the following order: (1) protection from the environment; (2) medium of group acceptance; (3) extension of self-image; (4) enhancement of sexual attraction; (5) indicator of status; (6) aesthetic and sensuous satisfaction. On the other hand, the respondents rated the failure of each function in this order; (1) protection from the environment; (2) extension of self-image; (3) aesthetic and sensuous satisfaction; (4) indicator of status; (5) enhancement of sexual attraction; and (6) medium of group acceptance. The result of the study suggest that clothing sever mainly for protection. Wearing clothes to to inculcate a sense of belonging is important, too. However, respondents still like to leave room for some individuality. In addition to this, respondents rated the aesthetic function being 6th in importance as a cause of satisfaction and its failure is rated as a cause of dissatisfaction. This means that the respondents do not choose clothes mainly for their aesthetic qualities; but lack of these qualities is a good cause of disappointment with these same clothes. Moreover, the small differences of the respondents' rating suggest that all of the functions count a lot for general satisfaction of purchased used clothing. In terms of dissatisfaction, the respondents rated the first function, that is, as protection from the environment as the most significant cause of dissatisfaction over a garment.